Da medicina não hospitalar ao hospital médico: uma leitura das análises de Michel Foucault sobre a história da medicina - Souza, Washington Luis (2008)
This study aims to present, having Michael Foucault s work as basis, to present the transition from classic medicine (centuries XVII and XVIII) to modern medicine (centuries XIX and XX), as a turning point, opposed to the teleologic evolution thesis proposed by the traditional medical historiography. On institutional basis, we will approach the dichotomy between medical practices and the classic hospital institutions, placing the creation of therapeutic hospital as a fact of modern age. This dissertation tries to show that classic medicine which classifies pathological species was a knowledge based in natural history and reached its top at the end of Classic Age, when the knowledge from biology, such as anatomy and physiology, were applied to the study of pathologies creating the modern empirical medicine. Modern medicine was constituted as a different knowledge with subject, object, concepts and methods completely distinct. However this change hasn´t happened due to the improvement of knowledge and practice, but because of studies that were developed outside the medical field, apart from the medical reason. Therefore it is not justificable to think about the history of medicine in terms of evolutionary continuity, being best described, on the contrary, as a discontinuous and not progressive history